Conocimiento y práctica de higiene bucal en adolescentes del caserío Santa Clara de Nanay Iquitos 2021 - Vela Vásquez, Ana Abigail (2023)
The research has been developed with the objective of determining the relationship between knowledge and practice of oral hygiene in adolescents from Caserío Santa Clara de Nanay, Iquitos 2021, whose research problem was the following: Is there a relationship between knowledge and practice of oral hygiene? oral hygiene in adolescents from Caserío Santa Clara de Nanay, Iquitos 2021? Methodology, the study was quantitative with a non-experimental, correlational and cross-sectional design, the sample was made up of 60 adolescents from 12 to 18 years of age of both sexes, the techniques that were used were the interview, observation and home visit, the instruments were the oral hygiene knowledge questionnaire, which had 98.32% validity and 96.0% reliability, and the oral hygiene practice checklist, which had 98.09% validity and 96.2% reliability. The results indicate that 76.7% low knowledge and 23.3% high knowledge; in oral hygiene practices, 88.3% bad and 11.7% good, it was obtained (X2 = 38.758, p = 0.000 < 0.05, gl = 2 with 95% confidence level). Therefore, it is concluded that there is a significant statistical relationship between the knowledge and practice of oral hygiene in adolescents from Caserío Santa Clara de Nanay, Iquitos 2021.